HEMODYNAMIC INSIGNIFICANT CAROTID ARTERIES STENOSIS AND RISK OF EMBOLIC STROKE IN PATIENTS WITH ISCHEMIC HEART DISEASE - V. V. Semenova; A. N. Zakirova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To assess a risk of vascular embolism in patients with ischemic heart disease (IHD) and hemodynamic insignificant asymptomatic carotid stenosis.Material and methods. 100 patients with IHD were examined. Ultrasound scanning of the main cranial arteries and transcranial Dopplerography was performed in all patients as well as lipid spectrum, fibrinogen level and blood D-diameter concentration were evaluated.Results. 165 carotid atherosclerotic plaques (AP) were detected in patients with IHD independently on angina severity. In IHD patients with nonhomogeneous hypoechogenic AP microembolic signals (MES) were revealed in 44,78%, with nonhomogeneous hyperechogenic AP - in 25%, with homogeneous hypoechogenic AP - in 4,16% of patients. MES were not recorded in patients with homogeneous hyperechogenic AP. There were not relations between MES and parameters of lipid spectrum as well as fibrinogen and Ddiameter plasma levels.Conclusion. Thus, during transcranial dopplerographic monitoring MES were recorded in the third part (27,9%) of IHD patients with hemodynamically insignificant carotid arteries stenosis. MES were predominantly observed in patients with nonhomogeneous AP especially with hypoechogenic components.